Rationale of Employee Turnover: An Analysis of Banking Sector in Nepal - Chaudhary, Manoj Kumar (International Research Journal of MMC, 2022)
The main purpose of this study is to elaborate the reasons for employee turnover in the banking sector of Nepal .The study has opted both primary and secondary sources of data to achieve the objective of the study. The structured questionnaires were used to collect the data from the sample banks. Meanwhile, different published and unpublished reports of the selected banks were used for the analysis. The collected data were analyzed with the help of MS-excel, and SPSS descriptive statistics. The finding of the study emphasized that employees tend to leave their current jobs due to the lack of proper environment and facilities provided by the banks. This study concludes that the Managers in the sample banks to some extent lack awareness regarding the prediction of employees’ turnover intentions. Hence, it is recommended to make clear policies and a proper plan with reference to the effective payment & reward schemes and motivational strategies to minimizethe employees’ turnover.